well, let me put it this way.
[tex]r^2=x^2+y^2\qquad \qquad \qquad \theta =tan^{-1}\left( \cfrac{y}{x} \right) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (\stackrel{x}{\sqrt{3}}~~,~~\stackrel{y}{\sqrt{3}})\qquad \qquad \begin{array}{llll} \stackrel{\textit{is assuming that}}{r^2=(\sqrt{3})^2+(\sqrt{3})^2}\implies r=\sqrt{(\sqrt{3})^2+(\sqrt{3})^2}\\\\ \stackrel{\textit{is also assuming that}}{\theta =tan^{-1}\left( \cfrac{\sqrt{3}}{\sqrt{3}} \right)}\implies \theta =tan^{-1}(1)\implies \theta =\cfrac{\pi }{4} \end{array}[/tex]